Charles Wheeler, By-Laws of the Village of Mechanicville 7 (1881) - (:unkn) unknown (My University, 1881)
Fires and Their Prevention, Fire Arms and Fire Works, § 20: No person, except on the anniversary of our national independence, and on that day only, at such place or places as the President or Trustees shall permit, shall fire, discharge or set off, in the village, any gun, cannon, pistol, rocket, squib, cracker or fire ball, under the penalty of five dollars for each offense.
Keywords: DISCHARGE